Effects of standard training in the use of closed-circuit televisions in visually impaired adults: design of a training protocol and a randomized controlled trial - van Rens Ger HMB; Melis-Dankers Bart JM; van Nispen Ruth MA; Burggraaff Marloes C (BMC, 2010)
Abstract Background Reading problems are frequently reported by visually impaired persons. A closed-circuit television (CCTV) can be helpful to maintain reading ability, however, it is difficult to learn how to use this device. In the Netherlands, an evidence-based rehabilitation program in the use of CCTVs was lacking. Therefore, a standard training protocol needed to be developed and tested in a randomized controlled trial (RCT) to provide an evidence-based training program in the use of this device. Methods/Design To develop a standard training program, information was collected by studying literature, observing training in the use of CCTVs, discussing the content of the training program with professionals and organizing focus and discussion groups. The effectiveness of the program was evaluated in an RCT, to obtain an evidence-based training program. Dutch patients (n = 122) were randomized into a treatment group: normal instructions from the supplier combined with training in the use of CCTVs, or into a control group: instructions from the supplier only. The effect of the training program was evaluated in terms of: change in reading ability (reading speed and reading comprehension), patients' skills to operate the CCTV, perceived (vision-related) quality of life and tasks performed in daily living. Discussion The development of the CCTV training protocol and the design of the RCT in the present study may serve as an example to obtain an evidence-based training program. The training program was adjusted to the needs and learning abilities of individual patients, however, for scientific reasons it might have been preferable to standardize the protocol further, in order to gain more comparable results. Trial registration http://www.trialregister.nl, identifier: NTR1031